Valuing recreational ecosystem service flow in Finland. (July 2015) - Lankia, Tuija; Kopperoinen, Leena; Pouta, Eija; Neuvonen, Marjo
Abstract: In this study we defined the spatial allocation for the value of recreation ecosystem services in Finland. The Finnish National Outdoor Recreation Demand Inventory, a representative survey dataset of Finnish recreationists and their recreation visits (last close-to-home visit and overnight nature trip), allowed us to estimate the annual number of recreation trips to various area types: (1) areas used under everyman׳s right, (2) state-owned recreation and nature conservation areas, and (3) leisure homes and their surroundings. To match the values for recreation visits with each area type in different parts of Finland, we applied the aggregate travel cost method. GIS was used to map the regional visits as well as their value. The results emphasize the relative importance of close-to-home recreation compared to overnight nature trips in terms of the total number of visits and their values. The spatial allocation of the value of close-to-home visits followed population density, while the type of ecosystem had a minor role. Our approach provides an example of how to utilize national recreation data, which are also available in some other European countries, to define and map the value of recreational ecosystem services. This information is becoming increasingly important for land use decisions as well as for national debates about the health benefits of outdoor recreation. Management Implications: This study documents the considerable value associated with the recreational use of ecosystems and how it can be used for natural resources policy and management. The analysis presented in this paper shows how a high quality recreational data set allows analysts – To discuss the value of recreational use in the context of other forms of land uses; – To use the information for national strategic recreational management as well as for national health strategies; – To integrate cultural ecosystem services in the spatial development of specific sites; – To use the information in environmental assessments, at least on a strategic level; and To discuss the quality of life on a regional basis.